2019
DOI: 10.1002/anie.201814412
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinear Optical Switching in Regioregular Porphyrin Covalent Organic Frameworks

Abstract: Covalent organic frameworks (COFs) have garnered immense scientific interest among porous materials because of their structural tunability and diverse properties. However,the response of such materials towardlaser-induced nonlinear optical (NLO) applications is hardly understood and demands prompt attention. Three novel regioregular porphyrin (Por)-based porous COFs-Por-COF-HH and its dual metalated congeners Por-COF-ZnCu and Por-COF-ZnNi-have been prepared and present excellent NLO properties.N otably,i ntens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
114
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 160 publications
(116 citation statements)
references
References 50 publications
2
114
0
Order By: Relevance
“…More recently,F eng et al have reported af amilyo fc onjugated 2D Pc-based MOFs exhibiting high electrical conductivityt hat were used for electrocatalysis. [207,208] Porphyrin- [209][210][211][212][213][214][215][216][217] and phthalocyanine-based [32,[218][219][220][221] COFs have also received al ot of attention in recent years due to their photocurrent generation properties and possible applications in optoelectronics. For example, ambipolar conducting 2D porphyrin-based COFs bearing different metalsw ere synthesized providing efficient charge transport pathways,w hich have adirect influence on their photoconductivep roperties.…”
Section: Porphyrin (Por)mentioning
confidence: 99%
See 1 more Smart Citation
“…More recently,F eng et al have reported af amilyo fc onjugated 2D Pc-based MOFs exhibiting high electrical conductivityt hat were used for electrocatalysis. [207,208] Porphyrin- [209][210][211][212][213][214][215][216][217] and phthalocyanine-based [32,[218][219][220][221] COFs have also received al ot of attention in recent years due to their photocurrent generation properties and possible applications in optoelectronics. For example, ambipolar conducting 2D porphyrin-based COFs bearing different metalsw ere synthesized providing efficient charge transport pathways,w hich have adirect influence on their photoconductivep roperties.…”
Section: Porphyrin (Por)mentioning
confidence: 99%
“…[212,215] More recently,e lectronic and optical properties of Por-based COFs have also been exploited towards energys torage [213] and NLO applications. [217] Phthalocyanines are also excellent building blocks for the preparation of functional COFs in optoelectronics.D ifferent crystalline boronate ester-linked Pc-based COFs have been prepared and some of them exhibitedh igh chargec arrier and photoconductivity. [219,220] Feng et al reported ad etailed study on the electronic properties of some metal-phthalocyanine-based pyrazine-linked 2D COFs exhibiting high mobility towards their use in electronics.…”
Section: Porphyrin (Por)mentioning
confidence: 99%
“…12 Moreover, the obtained figure of merit (FoM = s 1 /s 0 ; 5571) for the Por-TzTz-POF is also higher than that of our recently reported porphyrin based COFs; Por-COF-HH (FoM = 3534), Por-COF-ZnCu (FoM = 3565) and Por-COF-ZnNi (FoM = 3762), tabulated in Table S2 (ESI †). 11 Overall, these results signify a structure-activity relationship in porphyrin based porous organic materials that can be useful in optical switching applications. 16,17 In summary, we have synthesized a conjugated TzTz-linked porphyrin organic framework employing single-step direct condensation of A4 porphyrin tetra-aldehyde and DTO.…”
mentioning
confidence: 70%
“…It is worth Fig. 1 Schematic representations of the synthesis of the Por-TzTz-POF and Por-CQN-COF (previously reported as Por-COF-HH), 11 (b) and (c) experimental (red) PXRD profiles of the Por-TzTz-POF and Por-CQN-COF (the black pattern is the simulated one derived from the eclipsed model) respectively with molecular models (C: grey; N: blue; S: yellow and H: white).…”
mentioning
confidence: 99%
“…Up to date, a huge variety of 2D COF structures has been synthesized and studied, e.g., in the direction of photoactivity and photosensitivity. [61,78,[82][83][84][85][86][87] However, electronic structures are seldom discussed and, even then, mostly only single layers are considered. [60,[88][89][90] Thomas et al [60,90] investigated electronic structures of 2D -conjugated polymers with three-and fourarm connections, which correspond to kagome and Lieb (Archimedean) lattices, and explained occurrence of flat and disperse bands.…”
Section: Stacking Of 2d Covalent Organic Frameworkmentioning
confidence: 99%